Public Procurement and Precautionary Measures - Carpio Ramírez, Carlos (2015)
In the present paper, the author analyses some problems that he considers relevant on the field of the public procurement on Peru and Latin America. Parting from the problems on the application of the Public Procurement Law in Peru, he proposes the installation of a new instance that watches for the right behavior of supervisor entities of public procurement.